Effectiveness Assessment of Adaptation Measures to Build Wildfire Resilience of Road Networks - ICASP14; Arango, Erica; Nogal, Maria; Yang, Ming; Sousa, Helder; Stewart, Mark; Matos, Jose (My University, 2023)
Wildfires have become a source of concern for society due to their increased frequency, intensity, and unpredictability. This has caused serious impacts all over the world, even in areas where this type of problem has not occurred before. Studies on the adaptation of critical infrastructure have been conducted to reduce the impacts of this type of hazard caused by climate change. However, there are currently no tools to evaluate adaptation measures and their influence on the wildfire resilience of transportation infrastructure. Therefore, this paper proposes the application of a simplified methodology to assess the priority level of intervention in bridge networks and the effectiveness of different adaptation measures. The above is applied to a Portuguese case study. In that sense, the results show that adaptation measures such as changing vegetation management policies and implementing wildfire spread barriers effectively reduce the exposure of bridges. Therefore, this tool can be very useful for stakeholders and practitioners supporting wildfire management in terms of adaptation measures.
14th International Conference on Applications of Statistics and Probability in Civil Engineering(ICASP14)
PUBLISHED